Dangdut Koplo as a Manifestation of Popular Culture In Indonesia - Rustanta, Agustinus (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
One of the original works of Indonesians is dangdut music, more specifically, dangdut koplo. Dangdut music continues to grow, and the coming of dangdut koplo is accompanied by the human invention of information and communication technology, namely social media. This technology has succeeded in having a positive impact on the work of the nation, namely spreading dangdut koplo to all corners of the islands and even to the corners of the world. The objective of this simple piece of writing is to highlight a popular culture that occurs in Indonesia. One of the results of human thought, especially that of the people of East Java, in terms of art, especially music, can be a type of music that is light, pleasing to the ear, favored by people of all ages, strata, and social statuses, is able to eliminate all kinds of barriers in society, and can be an alternative form of entertainment. The objective of the study is to describe a new culture which emerged from the grassroot but it attracts international attention. The method used is the observation of communication phenomena that occur in society and literature study, which are then linked into propositions that can be used as subjects for the development of the scientific repertoire of culture and communication. It can be concluded that the emergence of dangdut koplo is clear evidence that everyone can produce a work that can be enjoyed by many people and can become a new culture in society that does not discredit previous works but instead strengthens and perfects previous great works.